2011
DOI: 10.1057/ejdr.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

‘From School to Adulthood’? Young People's Pathways Through Schooling in Urban Ethiopia

Abstract: This article presents a case study of a rapidly evolving urban community in Southern Ethiopia drawing on survey and qualitative data from Young Lives, a long-term international study of two cohorts of children growing up in poverty (born 1994-1995 and 2000-2001). It uses this to set visible changes in aspirations and experiences of schooling over time in their political and economic context. The article illustrates the value of mixed-methods approaches within international development research by juxtaposing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In line with other research with children and young people in Ethiopia, this research found children in Hawassa children to value education as essential to their current and future wellbeing (Boyden, 2013;Camfield, 2011). Participants had clear ideas about why they wanted go to school, and about how education was and would help them in the present and in the future.…”
Section: Findings and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with other research with children and young people in Ethiopia, this research found children in Hawassa children to value education as essential to their current and future wellbeing (Boyden, 2013;Camfield, 2011). Participants had clear ideas about why they wanted go to school, and about how education was and would help them in the present and in the future.…”
Section: Findings and Discussionsupporting
confidence: 77%
“…Children's narratives about their education were analysed in order to explore their motivations for going to school and where these motivations came from, and to identify potential functions for education in this context. They were not taken as 'truth' in terms of what education was and would actually achieve for these children, and in many instances children's high expectations, for instance for prestigious and professional employment outcomes, were likely to remain unfulfilled (Camfield, 2011;Tafere, 2014).…”
Section: Insert Table 1 Around Herementioning
confidence: 99%
“…While these shifting expectations are observed for all four countries, they are especially marked in Ethiopia, where unemployment is as high as 50% in some urban areas, and employment opportunities for girls in the formal skilled labour market are particularly scarce (Camfield, 2011). Perceptions of social risk result in further constraints for girls Camfield, and Tafere, 2011).…”
Section: : Inequalities During Middle and Later Childhoodmentioning
confidence: 95%
“…The current generation of Ethiopian youth is the first to receive access to primary education on a wide scale; net enrollment rates increased from 21 to 93 percent over the last two decades (UN ). This rapid educational transformation seems to coincide with another important shift: an aspirational orientation away from rural, agrarian livelihoods toward urban, professional futures (see Abebe ; Tadele and Gella ; Camfield ; Maurus ). Although Ethiopia remains one of the least urbanized countries in Africa—with some 80 percent of its population living in rural areas, compared to an average of 62 percent in sub‐Saharan Africa—the country is urbanizing quickly, at a rate of 4.9 percent (2010–2015 estimate), and the economic, educational, and demographic transitions unfolding in Ethiopia augur significant shifts for the movement of its populations.…”
mentioning
confidence: 99%